Ready for first : - Norris, Roy (Macmillan, 2015)
This step-by-step approach ensures that students will be fully prepared and confident when sitting the new 2015 First Certificate exam. The Student's Book, available with or without key, contains 14 units and now includes a 'Writing Bank'. The accompanying Student's Book DVD-ROM contains two computer-based practice tests and video material for the Speaking test.